Luminescent molecules towards precise cellular event regulation. Issue 70 (4th August 2020) - Hu, Ming; Han, Qinyu; Lyu, Linna; Tong, Yan; Dong, Shuo; Loh, Zhi-Heng; Xing, Bengang
Abstract : A unique lanthanide complex which responds to near-infrared (NIR) stimulation was developed for remote regulation of cellular events. Abstract : A unique lanthanide complex which responds to near-infrared (NIR) stimulation was developed for remote regulation of cellular events. This molecule can be localized specifically on the cell surface. Upon NIR stimulation, strong emission of the complex can successfully modulate the activities of light-gated membrane channels and regulate the ion flux in vivo .